Improving Cyber Security of Internet Web Gateway using NIST Framework - Fahmy, Azzam (Swiss German University, 2019)
The internet utilization is become more growth for every years where the cyber-attack also taking part into risk in the organization. The existing cyber security infrastructure (Web gateway) shall be replacing to answer adequate of respond to threat, Vulnerabilities or viruses. Therefore company using NIST Framework [1] to improving Infrastructure Cyber Security thru identification of risk. The framework will help Company to identify, asses and managing cyber security risk in regards with replacing the old Web Gateway. And future outcomes of the replacement of Internet web gateway shall address the current and future profile and managed security program base on risk evaluation.